Dark and Bright Excitons in Halide Perovskite Nanoplatelets. Issue 5 (23rd December 2021) - Gramlich, Moritz; Swift, Michael W.; Lampe, Carola; Lyons, John L.; Döblinger, Markus; Efros, Alexander L.; Sercel, Peter C.; Urban, Alexander S.
Abstract: Semiconductor nanoplatelets (NPLs), with their large exciton binding energy, narrow photoluminescence (PL), and absence of dielectric screening for photons emitted normal to the NPL surface, could be expected to become the fastest luminophores amongst all colloidal nanostructures. However, super‐fast emission is suppressed by a dark (optically passive) exciton ground state, substantially split from a higher‐lying bright (optically active) state. Here, the exciton fine structure in 2–8 monolayer (ML) thick Cs n − 1 Pb n Br3 n + 1 NPLs is revealed by merging temperature‐resolved PL spectra and time‐resolved PL decay with an effective mass model taking quantum confinement and dielectric confinement anisotropy into account. This approach exposes a thickness‐dependent bright–dark exciton splitting reaching 32.3 meV for the 2 ML NPLs. The model also reveals a 5–16 meV splitting of the bright exciton states with transition dipoles polarized parallel and perpendicular to the NPL surfaces, the order of which is reversed for the thinnest NPLs, as confirmed by TR‐PL measurements. Accordingly, the individual bright states must be taken into account, while the dark exciton state strongly affects the optical properties of the thinnest NPLs even at room temperature. Significantly, the derived model can be generalized for any isotropically or anisotropically confined nanostructure. Abstract : 2D semiconductor nanoplatelets can enable faster and more efficient light‐emitting devices. For this, a detailed understanding of their energetic structure is paramount. Here, the thickness‐dependent exciton fine structure of nanoplatelets is deduced by merging temperature and time‐resolved photoluminescence spectroscopy with a novel effective mass model, considering anisotropic quantum and dielectric confinement. Relevantly, the model can be generalized for any nanostructure.